2018
DOI: 10.1007/s00415-018-8835-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome of acquired demyelinating syndromes in Dutch children: update of a nationwide and prospective study

Abstract: IntroductionAcquired demyelinating syndromes (ADS) are immune-mediated demyelinating disorders of the central nervous system in children. A nationwide, multicentre and prospective cohort study was initiated in the Netherlands in 2006, with a reported ADS incidence of 0.66/100,000 per year and MS incidence of 0.15/100,000 per year in the period between 2007 and 2010. In this study, we provide an update on the incidence and the long-term follow-up of ADS in the Netherlands.MethodsChildren < 18 years with a first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 37 publications
(55 reference statements)
4
43
0
2
Order By: Relevance
“…Autoimmune encephalitis (AIE) has expanded the already comprehensive list of pediatric neuroinflammatory disorders of the CNS. Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis and acute disseminated encephalomyelitis (ADEM) are the most frequently described cause of AIE in children, [1][2][3][4] and disease courses have been studied in detail, including treatment responses, functional recovery, 1,4 and long-term neuropsychological outcome. 5 Next to anti-NMDAR, other neuronal antibodies have been described only sporadically in children, [6][7][8] whereas in adults, reported incidence of these antibodies has increased dramatically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoimmune encephalitis (AIE) has expanded the already comprehensive list of pediatric neuroinflammatory disorders of the CNS. Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis and acute disseminated encephalomyelitis (ADEM) are the most frequently described cause of AIE in children, [1][2][3][4] and disease courses have been studied in detail, including treatment responses, functional recovery, 1,4 and long-term neuropsychological outcome. 5 Next to anti-NMDAR, other neuronal antibodies have been described only sporadically in children, [6][7][8] whereas in adults, reported incidence of these antibodies has increased dramatically.…”
Section: Resultsmentioning
confidence: 99%
“…This category consisted partially of children with clinically defined acquired AE/inflammatory disorders, such as Rasmussen encephalitis or Sydenham chorea, and partially of children with MRI or CSF abnormalities pointing toward an AE/inflammatory etiology (pleocytosis, elevated protein, or oligoclonal bands in CSF, and MRI lesions in the temporal lobe), with exclusion of other causes, and not fulfilling the criteria of seronegative AIE. 11 (4) Unknown etiology and no support for AE/inflammatory, including children without MRI or CSF abnormalities pointing toward and AE/inflammatory etiology. 5…”
Section: Definitionsmentioning
confidence: 99%
“…Studies have reported an incidence of MS in children between 0.26 and 2.1 per 100,000 children, depending on the geographic location. [6][7][8][9][10][11] Some of these studies have reported a rising incidence of MS in children; however, improved awareness of the diagnosis and changes in diagnostic criteria likely impact these estimates.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…In brief, patient serum (1:50) was incubated with a transduced cell line expressing full-length human MOG, followed by fluorochromeconjugated anti-human IgG (H+L). Dilution of serum at 1:50 was standard and was most frequently used across studies (2,3,6,8,23,24,30,32,38) Table 2). Samples were reported positive if they were above the positive threshold in at least two of three quality-controlled experiments, a feature that may not have been implemented in other studies but ensures a reliable serostatus report and provides insight into serostatus reproducibility (21).…”
Section: Detection Of Human Mog Ab By Flow Cytometrymentioning
confidence: 99%